2022
DOI: 10.23917/jep.v23i1.17183
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Literacy Rate and Women’s Labor Participation in ASEAN

Abstract: Women have an essential contribution to economic growth and development. However, according to data, the Gender Inequality Index (GII) is still relatively high in developing countries, so special attention should be paid to aspects of women’s empowerment, health, and participation in the labor market as an indicator in measuring GII. In women’s empowerment, women’s education and women’s literacy are thought to affect women’s labor force participation. This study aims to examine and analyze the effect of women’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Women have an essential contribution to economic growth and development. However, according to data, the Gender Inequality Index (GII) is still relatively high in developing countries, so special attention should be paid to aspects of women's empowerment, health, and participation in the labour market as an indicator in measuring GII (Al Faizah et al, 2022) Most empirical studies have shown that women's education is an influential variable determining female labour participation. In addition to women's education, it turns out that the level of women's literacy also influences the level of women's labour force participation.…”
Section: Participation Rate By Gendermentioning
confidence: 99%
“…Women have an essential contribution to economic growth and development. However, according to data, the Gender Inequality Index (GII) is still relatively high in developing countries, so special attention should be paid to aspects of women's empowerment, health, and participation in the labour market as an indicator in measuring GII (Al Faizah et al, 2022) Most empirical studies have shown that women's education is an influential variable determining female labour participation. In addition to women's education, it turns out that the level of women's literacy also influences the level of women's labour force participation.…”
Section: Participation Rate By Gendermentioning
confidence: 99%
“…In some cases, having a higher education level makes it easier for individuals or communities to absorb information and incorporate it into their daily lives [15]. In his research, [16] he found that the literacy rate or education is very important for workers, especially women, because the dominance of male workers is very high. With higher education, the quality of the workforce will be higher, and it will be easier to encourage them to work smartly.…”
Section: The Effect Of Workforce Education Level On the Amount Of Rem...mentioning
confidence: 99%
“…Moreover, In addition to women's participation in the labor market is significantly linked to the birth rate (Klasen et al, 2021). Since women are regarded as an important part of the economy, their participation in the labor market may change the birth rate (Al Faizah et al, 2022).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This is because working women plan their children's birth following their work commitments (Horwood et al, 2021). On the other side, women are regarded as an important pillar of the economy, and more human capital formation increases women's participation in the labor market, which may change the birth rate (Al Faizah et al, 2022). Hence, researchers highlighted the importance of examining the influence of women's participation in the labor market to determine the fertility rate in a region.…”
Section: Introductionmentioning
confidence: 99%